Gasing Mathematics Instruction For Enhancing Problem-Solving Skills In Elementary School Students - Hayati, Zikra; Nelli Satriani; Nelly Raharti; Hijriati (PGMI IAIN Lhokseumawe, 2024)
Mathematics is a difficult, scary, and boring subject because the teaching method used by teachers is still monotonous, so that it has an impact on students' mathematical problem-solving abilities which are still low in solving a problem. A problem is a problem that if we get it and have not been able to solve it, but have the desire to solve it. Therefore, the GASING mathematics learning method (easy, fun, and enjoyable) is used. The GASING mathematics learning method is a method that uses a simpler method, reduces the use of formulas but emphasizes real (concrete) learning and can be combined with logic. The purpose of this study was to determine whether there was an effect of using the GASING mathematics method on students' problem-solving abilities. This study was conducted at SD Negeri 54 Banda Aceh with a sample of 30 students in grade IV. The research method in this study was the pre-experimental design method with a one group pretest - posttest design. The results obtained from this study were an increase in the average value from 8.17 in the pretest to 10.93 in the posttest. This difference is strengthened based on the results of the t-test (paired sample t-test) with a sig value = 0.000 <0.05, then, the hypothesis value in this study is (????o) is rejected and (????????) is accepted because there is a difference between the two tests. So it can be concluded that the GASING mathematics method has an effect on the problem-solving abilities of fourth-grade students at SD Negeri 54 Banda Aceh.